2016
DOI: 10.1016/j.jcte.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Lipid disorders in patients with renal failure: Role in cardiovascular events and progression of chronic kidney disease

Abstract: The spectrum of lipid disorders in chronic kidney disease (CKD) is usually characterized by high triglycerides and reduced high dense lipoprotein (HDL), associated with normal or slightly reduced low dense lipoprotein (LDL)-cholesterol. This dyslipidemia is associated with an increased risk for atherosclerotic cardiovascular disease. Keys for the cardiovascular risk reduction in these patients are lowering the number and modifying the composition of the cholesterol-carrying atherogenic lipoprotein particles. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 74 publications
6
37
0
1
Order By: Relevance
“…In CKD populations, the relationship between TG level and risk of death remains uncertain, as does the relationship between TG and risk of progression to ESRD (45,46). In the present study, the TG level at baseline and its longitudinal change pattern were not associated with a rapid Supplemental Material can be found at: Fig.…”
Section: Discussionmentioning
confidence: 54%
“…In CKD populations, the relationship between TG level and risk of death remains uncertain, as does the relationship between TG and risk of progression to ESRD (45,46). In the present study, the TG level at baseline and its longitudinal change pattern were not associated with a rapid Supplemental Material can be found at: Fig.…”
Section: Discussionmentioning
confidence: 54%
“…In general, renal dysfunction changes the level, composition, and quality of these lipids in favour of a more atherogenic profile [18][19][20][21] . The characteristic lipid pattern in patients with CKD stage 3 or higher consists of hypertriglyceridemia [G] , low levels of high-density lipoprotein (HDL) cholesterol and variable levels of low-density lipoprotein (LDL) cholesterol and total cholesterol 18,19,[22][23][24][25] . However, different CKD stages, modes of dialysis and levels of proteinuria are associated with specific lipid profiles (Table 1).…”
Section: Headings We Have a Limit For [H2] Subheadings Of 39 Charactmentioning
confidence: 99%
“…One recent randomization analysis demonstrated that genetically higher HDL cholesterol concentration was associated with better kidney function based on large samples form the largest lipid and CKD cohorts [11]. Visconti L et al [38] also reported lipid disorders in CKD was characterized by reduced HDL-C, high triglycerides and normal or slightly reduced LDL-C level. The mechanism for the association is not entirely clear, previous studies showed that the HDL-C had the antioxidant, anti-inflammatory and antithrombotic functions, which would reduce atherosclerosis in renal arteries and other arteries, it may serve as the protector of the renal functions [39].…”
Section: Discussionmentioning
confidence: 99%